1986
DOI: 10.1126/science.3080806
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Metallothionein Is Functional in Yeast

Abstract: Expression of two monkey metallothioneins in yeast leads to complementation of both known functions of the endogenous yeast copperthionein gene, namely copper detoxification and autoregulation of transcription. The metallothionein-like proteins of higher and lower eukaryotes are therefore functionally analogous despite their dissimilar primary sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 7 publications
1
34
1
Order By: Relevance
“…We also showed that the lethality induced by a ySAG deletion could be fully complemented by human SAG, indicating conservation of function. Two RING motif-disrupted mutants, G1 factor needed for normal G1 phase 2.5 2.4 3.6 G1 regulation YGR129W (SYF2) Synthetic lethal with Cdc40 2.6 2.3 2.9 S/G2 control (Boger Nadjar et al, 1998) YGR188C (BUB1) Ser/thr protein kinase 2.0 2.0 2.2 G2/M checkpoint control (Farr and Hoyt, 1998) YJL030W (MAD2) Spindle-assembly checkpoint protein 2.5 2.8 3.5 Mitosis (Li and Benezra, 1996) (Thiele et al, 1986). In budding yeast, it is known that there is only one member of the ySAG/yROC/yRbx/Hrt family.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the lethality induced by a ySAG deletion could be fully complemented by human SAG, indicating conservation of function. Two RING motif-disrupted mutants, G1 factor needed for normal G1 phase 2.5 2.4 3.6 G1 regulation YGR129W (SYF2) Synthetic lethal with Cdc40 2.6 2.3 2.9 S/G2 control (Boger Nadjar et al, 1998) YGR188C (BUB1) Ser/thr protein kinase 2.0 2.0 2.2 G2/M checkpoint control (Farr and Hoyt, 1998) YJL030W (MAD2) Spindle-assembly checkpoint protein 2.5 2.8 3.5 Mitosis (Li and Benezra, 1996) (Thiele et al, 1986). In budding yeast, it is known that there is only one member of the ySAG/yROC/yRbx/Hrt family.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA blot analysis, 20 ,ug of each RNA sample was fractionated on a 1.5% agarose-formaldehyde gel, transferred to nitrocellulose, and hybridized with 32P-labeled probes (31). To detect CUP) gene-specific mRNA, a nick-translated CUP) XbaIKpnI DNA restriction fragment was used (41). ACE] mRNA was detected by using a nick-translated 1.8-kb HindIII DNA fragment purified from plasmid p2g by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…One such mechanism proposes the involvement of metallothioneins (MTs), which are intracellular cytoplasmic proteins containing high amounts of thiol groups as well as being rich in cysteine. These thiol groups are able to bind to several cytotoxic agents containing heavy metals (Thiele et al, 1986), such as cisplatinum. MTs appear to have a physiological role in the absorption, transport and metabolism of important trace metals, as well as a role in heavy metal detoxification.…”
mentioning
confidence: 99%